2022
DOI: 10.1021/acs.biomac.2c00907
|View full text |Cite
|
Sign up to set email alerts
|

High Drug Loading Nanoparticles Stabilized with Autologous Serum Proteins Passively Inhibits Tumor Growth

Abstract: We report drug nanocrystals stabilized with host-specific serum proteins with high loading (∼63% w/w). The human serum derived curcumin nanoparticles (Cur-NanoSera) showed superior in vitro anticancer efficiency compared to a free drug with substantial hemocompatibility. The preadsorbed protein coating impeded further protein corona formation, even with repeated serum exposures. Acute and subacute toxicity evaluations post single and dual injections of C57BL/6 mice indicated that Cur-NanoSera showed no promine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…26 Our group has recently developed autologous approaches to utilize host derived serum proteins as stabilizers of drug nanocrystals and metal quantum clusters broadly termed 'NanoSera'. 27,28 Considering the established preclinical safety of this approach, in the present work we involved autologous whole serum proteins to form gold nanodendrites, also named Plasmonic-NanoSera (PNS). This rapid and seedless one pot synthesis allows serum proteins to serve as both a template and stabilizer of the nanodendrites.…”
Section: New Conceptmentioning
confidence: 99%
“…26 Our group has recently developed autologous approaches to utilize host derived serum proteins as stabilizers of drug nanocrystals and metal quantum clusters broadly termed 'NanoSera'. 27,28 Considering the established preclinical safety of this approach, in the present work we involved autologous whole serum proteins to form gold nanodendrites, also named Plasmonic-NanoSera (PNS). This rapid and seedless one pot synthesis allows serum proteins to serve as both a template and stabilizer of the nanodendrites.…”
Section: New Conceptmentioning
confidence: 99%
“…18 Recently our group showed that API nanocrystals stabilized with autologous serum proteins with high drug loading (>60% w/w) termed 'NanoSera'. 19 Furthermore, we have demonstrated the stabilization of photo-active metal nanoparticles with autologous serum proteins with confirmed safety in mouse models. 20,21 Building on previous reports, an 'all-in-one' autologous therapeutic strategy has been formulated, emphasizing the predominant utilization of host-derived biomaterials in the development of a hybrid fibrin glue.…”
Section: Introductionmentioning
confidence: 74%
“…While albumin is a known drug carrier, apolipoproteins provide a stealth effect counterbalancing the opsonization effect of the globulins. 19,20,35,36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior study utilized host derived serum protein to form nanovesicles for patient specific nanomedicines 36 . Our group recently showed that drug nanocrystals can be directly stabilized with autologously derived serum proteins for cancer therapy 37 . This approach takes advantage of the endogenously derived proteins that are less likely to cause inflammatory response in addition to being eventually metabolized safely by the body.…”
Section: Introductionmentioning
confidence: 99%